Pendekatan Reward Dan Punishment Dalam Pembelajaran Pendidikan Agama Kristen Untuk Meningkatkan Motivasi Belajar Siswa - Tefbana, Abraham; Sanjaya, Agus (STT Pelita Dunia, 2024)
Abstract: The purpose of this study was to determine the relationship between giving reward and punishment with increasing student motivation in learning Christian Religion Education. This research is based on Skinner's theory of operant conditioning (responsive behavior habituation). This study uses a qualitative descriptive method approach to explain the impact of reward and punishment as a strategy to increase student motivation in learning Christian Religious Education. Giving reward and punishment is a teacher's response behavior to increase student motivation in Christian Religious Education subjects. The results of this study indicate that giving rewards to outstanding students and punishing students who are not disciplined in learning, has a positive impact on increasing student motivation in learning Christian Religion Education.